The immediate wound‐induced oxidative burst of Saccharina latissima depends on light via photosynthetic electron transport. Issue 3 (14th May 2015) - McDowell, Ruth E.; Amsler, Margaret O.; Li, Qian; Lancaster, Jack R.; Amsler, Charles D.; Bassi, R.
<x xml:space="preserve">Abstract</x> Reactive oxygen species (ROS) produced by an oxidative burst are an important component of the wound response in algae, vascular plants, and animals. In all taxa, ROS production is usually attributed solely to a defense‐related enzyme like NADPH‐oxidase (Nox). However, here we show that the initial, wound‐induced oxidative burst of the kelp Saccharina latissima depends on light and photosynthetic electron transport. We measured oxygen evolution and ROS production at different light levels and in the presence of a photosynthetic inhibitor, and we used spin trapping and electron paramagnetic resonance as an orthogonal method. Using an in vivo chemical probe, we provide data suggesting that wound‐induced ROS production in two distantly related and geographically isolated species of Antarctic macroalgae may be light dependent as well. We propose that electron transport chains are an important and as yet unaddressed component of the wound response, not just for photosynthetic organisms, but for animals via mitochondria as well. This component may have been obscured by the historic use of diphenylene iodonium, which inhibits not only Noxes but also photosynthetic and respiratory electron transport as well. Finally, we anticipate physiological and/or ecological consequences of the light dependence of macroalgal wound‐induced ROS since pathogens and grazers do not disappear in the dark.